Impact of entrepreneurial orientation on small business performance: moderating role of government intervention - Alhnity, Haitham; Mohamad, Armanurah; Ku Ishak, Awanis (2016)
This study aims to examine and observe the connections between the global entrepreneurial orientation (EO), the influence of Jordanian Government’s EO intervention towards the performance of the local small business industry as well as the impact of the intervention.A survey was conducted using questionnaires.The questionnaires were distributed to 384 entrepreneurs from a Jordanian entrepreneurial body known as ERADA.Questionnaire survey results indicate that Jordanian small business owners are in need to adopt EO to realize better business performance.Questionnaire survey result also suggested a check on the influence of Jordanian Government’s intervention on the relationship between EO and business performance